THE FACTORS OF SOCIAL PEDAGOGUE’S CAREER TRAJECTORIES - Stanišauskienė, Vilija; Edintaitė, Gintarė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Career is one of the most important sources of personality self-awareness, self-esteem, self-expression, social status and life income. Human satisfaction with their career affects all areas of life. The balance of human life depends on career, which consists of the most important areas of human life: love, finances, social activity, leisure, physical environment, personal and spiritual development and health (Clawson, 2010). Career is the attitude and human behaviour related with work experience throughout life. Career trajectory is perceived like professional life and work experience of personality projection in his/her biography. It highlights the human career stages, values and career satisfaction dynamics. Human career trajectory is determined by internal (education, qualification, aims, expectations, personal attitudes and values) and external (social, economic, political) factors. There are still not enough research that are intended to reveal the specific factors of professions and career trajectories. Therefore, what does the career trajectory of social pedagogue look like? What factors determine the particular profession career? These are the research questions of this article.The object of research - social pedagogues’ career trajectory. The aim - to reveal the factors of social pedagogue’s career trajectories. The article consists of three parts. In the first one it is theoretically the factors of social pedagogue career are grounded. In the second the research design is rationalized. The third is dedicated to the factors those influence the career trajectories of social pedagogues. Research methods: the analysis of scientific literature; semi-structured interview; qualitative content analysis. The results of research revealed that the trajectory of social pedagogue is determined by both internal and external factors. Trajectory has a clear layout in time, there are turning points, changes; each career stage is determined by various internal and external factors.